Review Update on Pneumococcal Conjugate Vaccine: A New Hope for Reduction of Pneumococcal Disease in Bangladesh - Fardows, Jannatul; Siddique, Abu Bakar; Farhana, Nasren; Islam, Tasmine Binte (Bangladesh Journal of Infectious Diseases, 2017)
Pneumococcal diseases are the common and widely distributed disease in the world. It causes various mortality and morbidity every year, mainly in the developing countries. Pneumococcal conjugate vaccine (PCV) is the new vaccine against all invasive pneumococcal diseases. PCV10 and PCV13 are the available preparation in worldwide. It is safe, highly antigenic and minimal side effects. In Bangladesh, PCV is included in EPI schedule from April 2015. The current preparation is Synforix PCV10, which is given intramuscularly with the pentavalent vaccine in EPI schedule. In conclusion, the assessment of PCV impact in Bangladesh requires national and regional level surveillance and the introduction of PCV in EPI will reduce the mortality and morbidity of the pneumococcal disease. Bangladesh J Infect Dis 2015;2(1):19-22